(untitled) (City: History, Culture, Society, 2021)
The article considers the process of mythologizing the historical past through the use of folk memory. Necropolises became one of the objects of mythologizing. Today there are almost no necropolises of the old Cherkasy region left. Among the most significant of them is the tomb of Bohdan Khmelnytsky and his son. Some of the necropolises among the population and among scientists have developed stable ideas as real. First of all, they are connected with the history of the Ukrainian Cossacks. But the most famous Cossack necropolises did not really exist. This applies to burials in Trakhtemir and Kaniv. In the first are mostly burials of the XIX century, which are not Cossack. There was never a Cossack necropolis in Kaniv. It is traditionally believed that Ivan Pidkova, Yakiv Shah, Samiylo Kishka and other Cossacks were buried here. But in fact, it is a myth created by historians and popular beliefs. A peculiar example of the necropolis of the old Cherkasy region is the burial of St. Macarius Tokarevsky, who was killed in 1678 during the capture of Kaniv by Turkish troops. The burial of Bohdan Khmelnytsky in Subotov should also be considered special. After all, only his whereabouts are known to this day, but the grave itself has not been found yet. It should be noted that folk ideas are quite approximate and do not give historical science accurate and reliable information.